Responsibility of Business Actors in regards to Motorbike Transportation as a Public Transportation Based on Applications - Yafi Romli, M. Al; Purwaningsih, Prihatini; Mustika, Desty Anggie (Universitas Ibn Khaldun Bogor, 2023)
This journal discusses the responsibilities of businesses operating motorcycle taxis as public transportation using an app-based system. The purpose of this journal is to analyze the legal aspects related to the operation of motorcycle taxis as app-based public transportation and to discuss the obligations of businesses in carrying out operational activities and providing services to users. This research uses a normative juridical research method to analyze and assess the legal aspects related to the operation of motorbike services as app-based public transportation. It also identifies the legal obligations that must be complied with by business operators in operating motorbikes as public transportation. The research findings indicate that the operation of motorbikes as app-based public transportation entails specific obligations and significant responsibilities, particularly regarding security, data confidentiality, and customer protection. Therefore, business operators who operate motorbikes as app-based public transportation have an obligation to ensure that their operational activities comply with applicable regulations and adhere to the obligations established in consumer protection laws. This journal provides recommendations that effective law enforcement and the dissemination of knowledge about the rights and obligations of service users and business operators can help ensure that motorbikes as app-based public transportation provide optimal benefits to society.